The Effect of Product Quality and Price on Customers’ Loyalty through Customers’ Satisfaction: The Case of Selling Region II, PT Wijaya Karya Beton Tbk - Fredyca, Andy; Rahayu , Sri; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research aims to determine the impact of product quality and price on customer loyalty through customer satisfaction in the Sales Region II PT Wijaya Karya Beton Tbk. The population is customers of the Sales Region II PT Wijaya Karya Beton Tbk with a sample or respondents of 190 people using a probability sampling technique with a cluster sampler system. The data used is primary data with the method of collecting query data and secondary data taken through literature. The analysis technique used by the researchers was structural equation modeling (SEM) using the Lisrel. The results of the research show that: 1) product quality has a positive and significant impact on customer satisfaction; 2) price has a significant and positive impact on client satisfaction, 3) product quality positively and significantly affects customer loyalty; 4) price has a positive and non-significant effect on customer loyalty, 5) customer satisfaction has a positive impact and significant influence on customer loyalties.